The Effect of the Poisson Ratio on the Yield Function in Plane Strain Condition - Niemunis, A. (Engineering Transactions, 1988)
Initial and subsequent yield surfaces are specified in the plane strain condition in terms of three stress components acting within the deformation plane and the state variable representing the lateral stress. The effect of the Poisson ratio on the yield condition is investigated. The rate constitutive relations are derived and applied to several simple cases.